Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.

Effectiveness of rodents as local seed dispersers of Holm oaks. (Oecologia, 2008)
In this study we assessed the effectiveness of rodents as dispersers of Quercus ilex in a patchy landscape in southeastern Spain. We experimentally followed the fates of 3,200 marked and weighed acorns from dispersal through the time of seedling emergence over three years. Rodents handled about 99% of acorns, and dispersed 67% and cached 7.4% of the dispersed acorns. Most caches were recovered and consumed, and only 1.3% of the original experimental acorns were found alive in caches the following spring. Dispersal distances were short (mean = 356.2 cm, median = 157 cm) and strongly right-skewed. Heavier acorns were dispersed further and were more likely to be cached and survive than lighter acorns. All caches were in litter or soil, and each contained a single acorn. Rodents moved acorns nonrandomly, mostly to oaks and pines. Most surviving acorns were either in oaks, a poor microhabitat for oak recruitment, or shrubs, a suitable microhabitat for oak recruitment. Our results suggest that rodents, by burying a relatively high proportion of acorns singly in shrubs and pines, act as moderately effective dispersers of Q. ilex. Nonetheless, this dispersal comes at a very heavy cost.

Irradiance and oak seedling survival and growth in a heterogeneous environment (Forest Ecology and Management, 2007)
The Mediterranean region emerges highly heterogeneous at every spatio-temporal scale. Key species shape a mosaic of patches (landscape units) composed of different microhabitats. Within these ecosystems irradiance appears as one of the most changing factors affecting communities’ dynamic. However, the impact of irradiance on the species performance is still poorly known. In this study, we intended to explore whether irradiance heterogeneity inﬂuences early recruitment. We chose a patchy Mediterranean site. During 2001, 2002 and 2003 we marked naturally Quercus ilex emerged seedlings. We distinguished three landscape units (Q. ilex woodlands, shrublands and afforestations) and six microhabitats (oak, broom, tall shrub, subshrub, pine and open). For each seedling, we measured (1) irradiance as global site factor (GSF); (2) acorn presence; (3) acorn depth; (4) burial layer; (5) distance to the nearest co-speciﬁc adult. As estimates of seedling performance, we measured seedling survival and height. Estimates of seedling performance were higher in 2001 and 2002 than in 2003. Oak or pine microhabitats achieved higher survival rates than brooms or open areas whilst under oaks, brooms or in open areas seedling height was lower than under tall shrubs. Irradiance signiﬁcantly affected seedling survival and growth. The lower the irradiance, the higher the survival. Maximal growth was found at intermediate irradiance, indicating that, in this system, moderate shade is crucial for Q. ilex seedling recruitment. Some microhabitats provide intermediate irradiance that combines positive effects on survival and growth. As a ﬁnal point, dispersers’ activity creates a heterogeneous distribution of acorn deposition ﬁltering out part of the total irradiance present in the study site.

Irradiance and oak seedling survival and growth in a heterogeneous environment - Puerta-Piñero, Carolina; Gómez, Jose M.; Valladares, Fernando (Forest Ecology and Management, 2007)
The Mediterranean region emerges highly heterogeneous at every spatio-temporal scale. Key species shape a mosaic of patches (landscape units) composed of different microhabitats. Within these ecosystems irradiance appears as one of the most changing factors affecting communities’ dynamic. However, the impact of irradiance on the species performance is still poorly known. In this study, we intended to explore whether irradiance heterogeneity inﬂuences early recruitment. We chose a patchy Mediterranean site. During 2001, 2002 and 2003 we marked naturally Quercus ilex emerged seedlings. We distinguished three landscape units (Q. ilex woodlands, shrublands and afforestations) and six microhabitats (oak, broom, tall shrub, subshrub, pine and open). For each seedling, we measured (1) irradiance as global site factor (GSF); (2) acorn presence; (3) acorn depth; (4) burial layer; (5) distance to the nearest co-speciﬁc adult. As estimates of seedling performance, we measured seedling survival and height. Estimates of seedling performance were higher in 2001 and 2002 than in 2003. Oak or pine microhabitats achieved higher survival rates than brooms or open areas whilst under oaks, brooms or in open areas seedling height was lower than under tall shrubs. Irradiance signiﬁcantly affected seedling survival and growth. The lower the irradiance, the higher the survival. Maximal growth was found at intermediate irradiance, indicating that, in this system, moderate shade is crucial for Q. ilex seedling recruitment. Some microhabitats provide intermediate irradiance that combines positive effects on survival and growth. As a ﬁnal point, dispersers’ activity creates a heterogeneous distribution of acorn deposition ﬁltering out part of the total irradiance present in the study site.
Keywords: light environment; Mediterranean Region; Quercus ilex; seedling performance; spatial heterogeneity